Complications and Functional Outcome Following Operative Treatment of Talus Neck and Body Fractures: A Systematic Review. Issue 3 (September 2022) - Wijers, Olivier; Posthuma, Jelle J.; Engelmann, Esmee W. M.; Schepers, Tim
Background: Central talar fractures are rare and often associated with impaired functional outcome. Despite recent advances in diagnosis and management of talus fractures, complications rates remain high and functional outcome is generally poor. This study aims to provide an overview of complication rates and functional outcome following operative treatment of talar neck and body fractures. This may help in clinical decision making by improving patients' expectation management and tailored treatment strategies. Methods: A systematic review of the literature was conducted of studies published from January 2000 to July 2021 reporting functional outcome and/or complications following operative treatment of talar neck, body, or combined neck and body fractures. Keywords used were (Talar fracture) or (Talus fracture). Data on complication rates and functional outcome was extracted from selected articles. Results: A total of 28 articles were included in our analysis reporting 1086 operative treated talar fractures (755 neck [70%], 227 body fractures [21%], and 104 combined body and neck fractures [9%]). The mean follow-up was 48 (range 4-192) months. Complications occurred frequently with; 6% surgical site infection, 8% nonunion, 29% avascular necrosis, 64% osteoarthritis, and in 16% a secondary arthrodesis was necessary. A wide variety in functional outcome was reported; however, there seems to be a correlation between fracture classification and postoperative complications. Conclusion: Operative treatment of central talar fractures is associated with a high incidence of early and late complications and often leads to an impaired functional outcome. Standardization of talar fracture classification and scoring systems in combination with large sample-sized prospective studies are warranted to detect further predictive factors influencing tailormade treatment strategies and patient expectation management. Level of Evidence: Level III, Systematic review of case series and case-control studies.